A Crystalline Diazadiborinine Radical Cation and Its Boron‐Centered Radical Reactivity. (24th May 2018) - Wang, Baolin; Li, Yongxin; Ganguly, Rakesh; Webster, Richard D.; Kinjo, Rei
Abstract: One‐electron oxidation of 1, 4, 2, 5‐diazadiborinine1 has been studied. While the reaction of1 a bearing phenyl groups on the B atoms with AgAlOC(CF3 )3 4 afforded a complex mixture, the same oxidation reaction with1 b featuring bulky mesityl substituents on the B atoms rendered the corresponding cation radical2 b as an isolable species. X‐ray diffraction analysis, EPR spectroscopy, and DFT calculations of2 b revealed the delocalization of the unpaired electron over the entire π‐system of2 b, as well as a large spin density (0.76 in total) on the two equivalent boron atoms. The chemical trapping reaction of2 b with p ‐benzoquinone and triphenyltin hydride afforded the dicationic species3 containing two newly formed B−O bonds and the monocationic product2b‐H containing a B−H bond, respectively, thus confirming the boron‐centered radical reactivity of2 b .